Impact of an Intervention Package for Preventing Anemia Among Adolescent Girls in Selected High Schools of Bangalore District - Chetan Kumar M R; G Nagarathnamma (RGUHS Journal of Nursing Sciences)
Background Anemia is the deficiency of red blood cells or hemoglobin leading to reduced oxygen transport in the body. It is a significant public health concern particularly among adolescent girls due to their increased iron needs during menstruation periods of growth and pregnancy.Objective The study was conducted to assess the levels of knowledge among adolescent girls regarding the prevention of anemia in selected high schools in Bengaluru district.Methods A quasi experimental approach with pretest - posttest design was adopted. Forty adolescent girls were selected through convenient sampling method using non-probability sampling approach.Result During the initial assessment in the experimental group 13 65 adolescent girls had inadequate knowledge while remaining 7 35 had moderate knowledge. In the control group 16 80 adolescent girls had inadequate knowledge and 4 20 had moderate knowledge. In the experimental group the pretest mean knowledge score regarding anemia prevention was 11.1 30.8 while the posttest mean score was 14.38 58 resulting in an improvement with an average enhancement score of 10.2 28.3. The study found a significant enhancement in the post-intervention knowledge levels regarding prevention of anemia among adolescent girls in the experimental group at a 5 level of significance.Conclusion The results of the study indicate that the intervention was effective in bringing about improvement in knowledge of anemia of the participants in the experimental group. A significant enhancement in knowledge was noticed in the intervention group compared to the control group highlighting the efficacy of a holistic approach to anemia prevention